Ultra-low-power, modular, class-AB current multiplier - Kongpoon, Metha (My University, 2019)
This paper describes a modular class-AB current multiplier which provides the good linearity, the linearly tunable conversion gain and the robustness to process mismatch. The proposed multiplier is derived from a hyperbolic sine multiplication identity, and was designed and simulated using 0.35 μm AMS CMOS process. Simulation results show that the improved linearity, linearly tunable conversion gain and better process variation robustness can be achieved while utilizing lower power consumption and the slightly higher number of transistors compared to the state-of-the-art class-AB current multiplier.
Keywords: class-AB; current mode; low-power; modularity; multiplier